Impact studies of shear thickening fluids incorporated within composite structures. (7th April 2011) - Trigg, C.; Dyke, A.; Davies, J.; Dunleavy, M.; Park, N.; Townsend, D.; Siggs, E.
Composite structures utilising fabric reinforcement are used routinely for a variety of applications including aerospace composites, body armour, sports equipment, etc. to improve their mechanical properties. The incorporation of shear thickening liquids into fabric systems has been investigated to evaluate the effects on the impact performance of these materials. Shear thickening fluids comprising particulate dispersions have been developed and incorporated into the fabric systems using a variety of infiltration techniques. Important parameters that have been shown to affect the performance include volume fraction, stability of the shear thickening fluid and the integration methods used to functionalise the fabric-based composite. Techniques to allow the characterisation of the impact performance of the shear thickening fluid have also been developed. The impact performance of infiltrated fabric-based structures has been shown to be improved by the incorporation of shear thickening fluids but is heavily dependent on the fluid particulate system and the integration techniques.